PERANAN WANITA/ISTRI NELAYAN DALAM USAHA MENGATASI PEREKONOMIAN KELUARGA PADA ERA NEW NORMAL DI KELURAHAN SINDULANG SATU KECAMATAN TUMINTING KOTA MANADO (Studi Kasus Kelompok Nelayan Daseng) - Soputan, Stevaldo J.M.; Manoppo, Victoria E.N.; Durand, Swenekhe S.; Rarung, Lexy K.; Tambani, Grace O.; Pangkey, Henneke (Universitas Sam Ratulangi, 2021)
AbstractSindulang Satu Village is one of the villages in Tuminting District which has a coastal area and most of the population works as fishermen. The job as a fisherman generates an uncertain income because it depends on the season and is currently pressured by government regulations in overcoming covid-19 and facing the new normal so that the participation of women as breadwinners to cover their household needs.How far their role is in dealing with the family economy is an interesting topic for conducting research. Research Objectives: 1. To analyze the economic condition of fishermen group households in Sindulang Satu Village, Tuminting District, Manado City. 2. To analyze the role of women in the household conomy of fishermen groups during the Covid-19 pandemic and facing the new normal era in Sindulang Satu Village, Tuminting District, Manado City. The method used in this research is the case study method. The data collected in this study are primary data and secondary data. The so-called respondents were obtained by recording all the women / wives of members of the Daseng fishermen group; and 15 people registered as the population. The 15 people who were used as respondents to be visited one by one conducted interviews with a questionnaire guide as a tool that had been previously prepared by means of a census. The data analysis used in this research is quantitative analysis and qualitative analysis.The economic condition of the family of the Daseng fishing group in Sindulang Satu Village includes age, education and family dependents. The women / wives of the Daseng fishermen group are mostly in the productive age range so they are still active in carrying out income-generating activities and jobs, their education is dominated by elementary school graduates, while the dependents of the family have at most 1 - 3 dependents in the family. The role of women / wives in overcoming the family economy of fishermen groups during the Covid-19 pandemic and facing the new normal era, including domestic roles, namely cooking, cleaning and tidying houses, caring for children and helping husbands, active social roles in spiritual activities (mother worship) also participate in arisan and PKK, and the productive role of women / wives of the daseng fishermen group is that they work as a washerman, open a shop and sell business. All the roles of the wife are very supportive of the economy of the Daseng group's fishing family. Keywords: Role of Women, Family Economy, Sindulang Satu AbstrakKelurahan Sindulang Satu merupakan salah satu desa di Kecamatan Tuminting yang memiliki daerah wilayah pesisir serta ada sebagian besar penduduk bekerja sebagai nelayan. Pekerjaan sebagai nelayan tersebut menghasilkan pendapatan yang tidak menentu karena tergantung kepada musim dan pada saat sekarang tertekan dengan peraturan pemerintah dalam mengatasi covid-19 dan menghadapi new normal sehingga peran serta wanita sebagai pencari nafkah untuk menutupi kebutuhan rumah tangga mereka.Seberapa jauh peranan mereka dalam rangka mengatasi perekonomian keluarga merupakan topik yang menarik untuk mengadakan penelitian. Tujuan Penelitian: 1) menganalisis keadaan perekonomian rumah tangga kelompok nelayan di Kelurahan Sindulang Satu Kecamatan Tuminting Kota Manado, dan 2) Menganalisis sejauh mana peran perempuan dalam perekonomian rumah tangga kelompok nelayan dimasa pandemic covid-19 dan menghadapi era new normal di Kelurahan Sindulang Satu Kecamatan Tuminting Kota Manado. Metode yang digunakan dalam penelitian ini adalah metode studi kasus. Data yang dikumpulkan dalam penelitian ini adalah data primer dan data sekunder. Adapun yang disebut sebagai responden diperoleh dengan cara mendata seluruh wanita/istri anggota kelompok nelayanDaseng; dan yangterdaftar berjumlah 15 orang yang disebut sebagai populasi. Ke 15 orang ini yang dijadikan responden untuk dikunjungi satu persatu mengadakan wawancara dengan panduan kuisioner sebagai alat bantuyang telah disiapkan sebelumnya dengan cara sensus. Analisis data yang digunakan dalam penelitian ini adalah analisis kuantitatif dan analisis kualitatif.Keadaan perekonomian keluarga kelompok nelayan Dasengdi Kelurahan Sindulang Satu meliputi keadaan umur, pendidikan dan tanggungan keluarga. Wanita/istri kelompok nelayan Daseng paling banyak dalam range umur produktif sehingga masih aktif dalam melakukan kegiatan dan pekerjaan yang menghasilkan pendapatan, pendidikan mereka didominasi oleh tamatan SD sedangkan tanggungan keluarga paling banyak memiliki 1 – 3 orang tanggungan dalam keluarga. Peranan wanita/istri dalam mengatasi perekonomian keluarga kelompok nelayan dimasa pandemic covid-19 dan menghadapi era new normal, meliputi peran domestik yaitu memasak, membersihkan dan merapikan rumah, mengurus anak dan membantu suami, peran sosial dengan aktif dalam kegiatan kerohanian (ibadah kaum ibu) juga mengikuti arisan dan PKK, dan peran produktif wanita/istri kelompok nelayan daseng ada yang bekerja sebagai tukang cuci, membuka usaha warung dan berjualan. Semua peran istri sangat mendukung perekonomian keluarga nelayan kelompok Daseng. Kata Kunci: Peranan Wanita, Perekonomian Keluarga, Sindulang Satu